IDENTIFYING SLANG WORDS IN MEGHAN TRAINOR’S SONG - Sakinah Sakinah (STBA Pontianak, 2017)
This study aims at analyzing existing slang words in Meghan Trai- nor’s song lyrics the data analyzed in this study are the slang findings in Meghan Trainor’s song lyrics. Those the main source of the data is Meghan Trainor’s song lyrics. The analysis was done in three stages, they are collecting the data, listing the category and presenting the results. The results showed some kinds of slang that are used and divided into three characteristics, they are clipping, blending and coinage. Clipping is a slang word spoken by shortening a word, blending mixes two words which have meanings which are then spoken in one word, while the coinage itself means creating a new word and that word became slang. The use of slang generally aims at creating interesting songs.